Упростите выражение: 5y(2y-1)-(3y-1)(3y+1)+[latex] (y-3)^{2} [/latex] И решите систему уравнения и сделайте проверку. [latex] \left \{ {{x+2y=6} \atop {5x-y=6}} \right. [/latex]
Упростите выражение: 5y(2y-1)-(3y-1)(3y+1)+[latex] (y-3)^{2} [/latex]
И решите систему уравнения и сделайте проверку.
[latex] \left \{ {{x+2y=6} \atop {5x-y=6}} \right. [/latex]
Ответ(ы) на вопрос:
Гость
№1. 10y^2-5y-(9y^2-3y+3y-1)+2y-6=0
10y^2-5y-9y^2+1+2y-6=0
y^2-3y-5=0
№2. x=6-2y
5(6-2y)-y-6=0
30-10y-y-6=0
-11y=-24
y=24/11
x=6-2*(24/11)=48/11
Не нашли ответ?
Похожие вопросы